Microanatomy of the digestive tract, hooves and some visceral organs of addax antelope (Addax nasomaculatus) following a concentrate or forage feeding regime. (8th March 2018) - Tahas, S. A.; Hetzel, U.; Altenbrunner‐Martinek, B.; Martin Jurado, O.; Hammer, S.; Arif, A.; Hatt, J.‐M.; Clauss, M.
Summary: Subacute ruminal acidosis is a common disease in captive non‐domesticated ruminants and is mainly diagnosed by rumen fluid pH and rumen histology. Furthermore, differences in ruminant gastrointestinal histology have been hypothesized to correlate with the browser–grazer continuum. Twelve surplus addax antelope ( Addax nasomaculatus ) were divided into two groups, fed either their usual diet, consisting of a concentrate feed with a limited amount of hay, or a diet of unlimited hay only, for 3 months. After culling, descriptive and morphometric histology and pH measurements were compared between groups. Significant variations in cellular subpopulations were noted between groups, with roughage‐fed individuals presenting primarily with balloon cells of the Stratum corneum and living layer cell vacuolization, whereas parakeratosis and intermediate‐type cells were more frequent in the concentrate‐fed group. Lesions typical of subacute ruminal acidosis were significantly more pronounced in concentrate‐fed individuals. Ruminal pH measurements did not differ significantly, but were more consistent in forage‐fed individuals, indicating a more stable reticuloruminal environment. The results indicate that ruminal histology may be more appropriate in assessing ruminal health compared to a single post‐mortem pH measurement. It is proposed that Stratum corneum balloon cells may indicate cell maturation and not, as previously assumed, hyperfunction. Concentrate‐fed individuals scored higher on the presence of inflammatory cells on hoof corium histology. The study further emphasizes the adaptability of ruminant digestive tract microanatomy in adult animals even after a short period of time and the positive effects an increased roughage diet may have in populations of captive grazing ruminants.